Penguraian Zat Warna Tartrazin pada Limbah Pencucian Mie Aceh Secara Ozonolisis dan Penyinaran Matahari dengan Penambahan Katalis ZnO - Bhayu Gita Bhernama (Al-Kimia, 2017)
People's habits in consuming Aceh noodles make the noodle industry grow rapidly, but the waste treatment process becomes less effective. In the process of making the noodles, dye waste is produced in the form of tartrazine dye and need to be processed before being disposed into the environment. The research purpose was to describe the decomposition of tartrazine using ozonolysis and solar radiation methods as one of the solutions in the waste treatment process. The use of ZnO as catalyst is to accelerate the decomposition reaction of the noodle washing wastes. The results of the analysis concluded that ozonolysis methods are more effective in decomposing tartrazine in the noodle wash wasted by solar irradiation method. The sun exposure decomposed tartrazine by 99.74% using 0.015 g ZnO for 150 min and tartrazine content obtained 0.022 mg/L with a sunlight intensity of 1.24 x 1016 cm-2 s-1. Ozonolisis exposure decomposed tartrazine by 98.68% using 0.020 g ZnO for 12 minutes and tartrazine content obtained 0.112 mg / L.